Exploring Non-CS Learners’ Experience in Brazil - Gomes, Renata Faria; Santos Junior, Ricardo Ferreira Dos; Garcia, Vinícius Cardoso (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2025: Anais do V Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2025.4889, 2025)
Non-CS learners are increasingly interested in programming for career opportunities, productivity, and better communication with technical teams. Despite well-known challenges like logical thinking, unique issues for non-CS learners remain underexplored. Purpose: This study examines the motivations, experiences, and challenges of Brazilian non-CS learners, aiming to inform educational strategies. Methodology: We conducted an open-ended survey with a diverse sample of 36 considered respondents, analyzing data through open coding. Findings: Key motivations include career advancement and job performance, with a preference for self-learning. However, non-CS learners encounter challenges with knowledge organization, discipline, and technical comprehension. his highlights the need for adaptable and personalized educational solutions that effectively support learners from diverse backgrounds. Recommendations: Students can leverage their original field’s expertise when transitioning careers or selecting relevant technologies enhancing future roles. Companies should support diverse backgrounds and provide tech training to non-technical staff to improve communication and productivity. Academic institutions may provide optional, field-integrated CS courses to prepare students with practical, applicable skills.